(3Md eTcdGJ GdeNJUQ deMeO GHf CHj GdLjT GdCfUGQjs - (3GdbjUQj, YHO GdeMSf Hf eMeO, J(B755(3g`s
(3ChdgG (B:s
(3GdMeO ddg Ydi Cf bUQ SdGeI GdWHY Ydi fhY GdEfSGf hCXgQ aj Wj UOhQge VQhH GdChRGfs
(3BNQgG (B:s
(3hCeG YfO GdNdjd adgG HMQ hGMO hgh GdeJbGQH hgPg UhQI GdOGFQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 152s
(3eYLe GdeDdajf(B: 2 / 312s
(3cTa GdXfhf(B: 2 / 1135s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdYQhV hGdbhGajs